Association analysis for quality attributes in ber (Ziziphus mauritiana L.) (Indian Journal of Arid Horticulture, 2025)
Yield being a complex character, is composed of several components, some of which affect the yield di- rectly while, others contribute towards it indirectly. Corre- lation studies provide an opportunity to study the magni- tude and direction of association of yield with direct and indirect quality parameters and also among these param- eters. To accumulate optimum combination of quality char- acters in a single genotype, it is essential to know the im- plication of the inter-relationship of various characters. Linear correlations between yield and various quality char- acters, because of the interrelationship among the compo- nents themselves can present a confusing picture. For this reason standard partial correlation or regression (path co- efficient) can give a more realistic interpretation of charac- ters involved. Considering these points in view, the present study was conducted to understand inter-relationship of the quality traits in ber.
Keywords: contribute; genotype; interrelationship; quality traits; accumulate; optimum